Identifikasi Motivasi Kader Dalam Menjalankan Tugas Di Posyandu Desa Planggiran Kec. Tanjung Bumi Kabupaten Bangkalan - Achmad Masfi; Muhammad Putra Ramadhan; Ronal Surya Aditya; Eri Yanuar Achmad Budi Sunaryo; Qory Tifani Rahmatika; Yhenti Widjayanti; Nurul Evi; Nurma Afiani (Jurnal Keperawatan Muhammadiyah, 2023)
Objective:    Posyandu success in facilitating and providing health services is the main goal of Posyandu. The government's efforts have not only increased the coverage of mothers and toddlers, but also increased the knowledge, skills, and motivation of the community, especially Posyandu health cadres. The aim of this research is to identify the motivation of cadres in carrying out posyandu activities.Methods:Research design The type of research used is analytic and the type of approach used is descriptive. The variables used were achievement, responsibility, supervision, mother's wishes, and relationships between friends, while the sample was 138 respondents using simple random sampling. The analysis was carried out univariately using frequency distribution tablesResults:  The results of the study based on the number of samples were 138 respondents, so the achievement variable showed that more than half of the samples had sufficient achievement, namely 79 people (57.2%). The responsibility variable is almost half having less responsibility, 67 people (48.6%). Supervision variable obtained more than half of non-routine supervision as many as 96 people (69.6%). The mother's desire variable has the sufficient category, almost half of 96 people (69.6%). While the relationship variable between friends is obtained, more than half of the cadres have less relationships as many as 75 people (54.3%) Conclusion:  Based on the results of the study, it was found that the motivation of cadres in carrying out posyandu activities could be increased in the variables in this study, namely achievement, responsibility, mother's wishes, relations between cadres and also supervision. The existence of cadres is important in posyandu activities, so there should be regulations and efforts to increase the motivation of cadres in carrying out posyandu activities. In addition, it is necessary to periodically evaluate and monitor the motivation of cadres.